Investigation on the Nonlinear Strength Properties and Damage Statistical Constitutive Model for Frozen Sandy Soils - De Zhang; Enlong Liu; Xingyan Liu; Ge Zhang; Xiao Yin; Bingtang Song (Advances in Materials Science and Engineering)
There are many flaws, such as fissures, cavities, and inclusions, in geomaterials, which make their mechanical properties with great randomness and uncertainty. Upon loading, the soil structure gradually losses the bearing capacity due to the transformation from microdefects to macroscopic breakage bands. Based upon the experimental data of frozen sandy soils, a new nonlinear strength equation between the first and third principal stresses was proposed, and then the nonlinear strength properties for frozen sandy soils in σ-τ plane were analyzed. In addition, by assuming that the microstrength of frozen sandy soil obeys the Weibull distribution function, a statistical damage constitutive model was established based upon the framework of continuum damage mechanics (CDM), with few parameters and a high accuracy. Compared with experimental data, the new model can well grasp the nonlinear strength properties and simulate the stress-strain relationships under different confining pressures for frozen sandy soils.